Brand transmission of spanish universities in their websites - Carrillo Durán, María Victoria; Castillo Díaz, Ana (Historia y Comunicación Social, 2014)
It starts from the idea that the image and well-managed communication are strategic assets which enhance the brand and, consequently, to the university. Transmission brand of Spanish universities through their web sites has become for universities in an issue of great importance due to the uncertainty in which the universities are located. In this sense, the web sites are not only the place where the public have a first contact with the university, but are also a means of communication with internal and external audiences, which allows institutions to ensure greater competitiveness, constitute an added value to their audiences.